Leishmaniasis: A Review of Transmission, Pathogenesis and Diagnosis - Abed , Zuhair Mohammed (American Journal of Biomedicine and Pharmacy, 2026)
Leishmania is an intracellular protozoan, belonging to the family Trypanosomatidae, documented across over 90 countries in the Middle East, Asia, South America along with Africa. Humans become infected with the Leishmania parasite through two source zoonotic source, where wild and domestic animals are important hosts and anthroponotic sources, in which humans act as the main hos of infection transmission. The sand fly is one of the most important vectors of the parasite, with 98 species of this genus recorded as being responsible for transmitting the disease, two of these species, Phlebotomus and Lutzomyia, have been confirmed to transmit the disease to humans. Approximately 53 species of the genus Leishmania was documented in various regions of the world, 14 species of Leishmania are transmitted from animals to humans. The severity of the leishmaniasis is affected by the parasite strain as well as efficiency of the hosts immune response, the infection is often asymptomatic, but in some cases it may develop into severe clinical manifestation that can be fatal if not treated appropriately. The Th1 response is a crucial factor in disease control, with both IFN-y and TNF-α stimulating macrophages, giving rise to parasite elimination or reduced replication.